Physico-Mechanical Properties Of Plywood Bonded By Nano Cupric Oxide (Cuo) Modified Pf Resins Against Subterranean Termites - Wei Gao; Guanben Du (Maderas: Ciencia y Tecnología, 2015)
Nano CuO and alkane surfactant modified phenol Formaldehyde (PF) resins were applied to manufacture plywood, and physical and mechanical properties, such as shear strength, tensile property, modulus of rupture (MOR), modulus of elasticity (MOE), as well as termite resistance were evaluated. The result showed that the combination of nano CuO and alkane surfactantplayed different effect on tensile strength, and especially on shear strength as evaluated at different test conditions. But it was confirmed to improve the water resistance of treated plywood specimens. The introduction of nano CuO and surfactant did not influence the flexural properties significantly by statistically. The result of termite tests indicated that the weight loss decreases gradually from 31,12% to less than 10,37%, and the mortality increases from 32,61% to higher than 86,35%. And the AWPA rating also rises from 4 (very severe attack) to 7 (moderate attack).